High endothelial venules are associated with microsatellite instability, hereditary background and immune evasion in colorectal cancer - Pfuderer, Pauline Luise; Ballhausen, Alexej; Seidler, Florian; Grabe, Niels; Knebel Doeberitz, Magnus von; Kloor, Matthias; Ahadova, Aysel (British journal of cancer, 2019)
BACKGROUND: Microsatellite-unstable (MSI) tumours show a high load of mutational neoantigens, as a consequence of DNA mismatch repair deﬁciency. Consequently, MSI tumours commonly present with dense immune inﬁltration and develop immune evasion mechanisms. Whether improved lymphocyte recruitment contributes to the pronounced immune inﬁltration in MSI tumours is unknown. We analysed the density of high endothelial venules (HEV) and postcapillary blood vessels specialised for lymphocyte trafﬁcking, in MSI colorectal cancers (CRC). - METHODS: HEV density was determined by immunohistochemical staining of FFPE tissue sections from MSI (n = 48) and microsatellite-stable (MSS, n = 35) CRCs. Associations with clinical and pathological variables were analysed. - RESULTS: We found elevated HEV densities in MSI compared with MSS CRCs (median 0.049 vs 0.000 counts/mm2, respectively, p = 0.0002), with the highest densities in Lynch syndrome MSI CRCs. Dramatically elevated HEV densities were observed in B2M-mutant Lynch syndrome CRCs, pointing towards a link between lymphocyte recruitment and immune evasion (median 0.485 vs 0.0885 counts/mm2 in B2M-wild-type tumours, p = 0.0237). - CONCLUSIONS: Our ﬁndings for the ﬁrst time indicate a signiﬁcant contribution of lymphocyte trafﬁcking in immune responses against MSI CRC, particularly in the context of Lynch syndrome. High HEV densities in B2M-mutant tumours underline the signiﬁcance of immunoediting during tumour evolution.